The Relationship Of Menstruation Knowledge With The Level Of Anxiety In Facing Menarche In School-Age Children In Central Magelang: Hubungan Pengetahuan Menstruasi Dengan Tingkat Kecemasan Dalam Menghadapi Menarche Anak Usia Sekolah Dikecematan Magelang Tengah - Oktavia, Finna Sela; Mareta, Reni; Wardani, Septi (Prosiding University Research Colloquium, 2024)
Background: Menarche is the beginning of reproductive development in children to adolescents. Lack of knowledge about menstruation can affect children’s readiness to face menarche and cause anxiety. The attitude of parents can affect the child’s readiness to face menarche. Knowledge about menstruation can help children prepare themselves better so as to reduce anxiety when facing menarche. Objective: This study aims to determine the relationship between the level of knowledge about menstruation and the level of anxiety in facing menarche in school-age children in Central Magelang District. Method: The research methodology used is quantitative with a cross-sectional design. The research sample consisted of 67 female students in grades IV, V, and VI who were selected through proportional random sampling. Data were obtained through questionnaires about the level of anxiety facing menarche and the level of knowledge about menstruation which were filled in directly. Results: The results showed that most female students (59.7%) had a good level of knowledge about menstruation. Meanwhile, most female students experienced anxiety in facing menarche, with a moderate level of anxiety (47.8%). Spearman Rank correlation test results obtained p value (0.002) ? (0.05), meaning that there is a relationship between knowledge about menstruation and anxiety facing menarche. Conclusion: It can be concluded that good knowledge about menstruation can also affect the level of anxiety in children. Thus it is suggested to increase knowledge about menstruation through appropriate sexual education in schools and involve the role of parents in providing accurate information about menstruation to their children.